Epidemiology of Plague: Problems with the Use of Mathematical Epidemiological Models in Plague Research and the Question of Transmission by Human Fleas and Lice - Ole J. Benedictow (Canadian Journal of Infectious Diseases and Medical Microbiology)
This article addresses the recent use of mathematical epidemiological SIR or SEIR models in plague research. This use of S(E)IR models is highly problematic, but the problems are not presented and considered. Serious problems show in that such models are used to “prove” that historical plague was a (1) Filoviridae disease and (2) a bacterial disease caused by Yersinia pestis which was transmitted by human fleas and lice. (3) They also support early-phase transmission (by fleas). They purportedly consistently disprove (4) the conventional view that plague is/was a rat-and-rat-flea-borne disease. For these reasons, the focus is on methodological problems and on empirical testing by modern medical, entomological, and historical epidemiological data. An important or predominant vectorial role in plague epidemics for human fleas and lice requires that several necessary conditions are satisfied, which are generally not considered by advocates of the human ectoparasite hypothesis of plague transmission: (1) the prevalence and levels of human plague bacteraemia (human plague cases as sources of infection of feeding human ectoparasites); (2) the general size of blood meals ingested by human fleas and lice; (3) the consequent number of ingested plague bacteria; (4) the lethal dose of bacteria for 50% of a normal sample of infected human beings, LD50; and (5) efficient mechanism of transmission by lice and by fleas. The factual answers to these crucial questions can be ascertained and shown to invalidate the human ectoparasite hypothesis. The view of the standard works on plague has been corroborated, that bubonic plague, historical and modern, is/was a rat-and-rat-flea-borne disease caused by Yersinia pestis. These conclusions are concordant with and corroborate recent studies which, by laboratory experiments, invalidated the early-transmission hypothesis as a mechanism of transmission of LDs to humans in plague epidemics and removed this solution to the problem of transmission by human fleas.